Development of Monitoring Parameters of Oxygen Concentration, Oxygen Flow Rate, Temperature and Humidity in IoT-Based CPAP Bubble (Oxygen and Humidity Concentration) - Ratna Ika Puspitasari; DYAH TITISARI; Lamidi Lamidi (Jurnal Teknokes, 2023)
Bubble Continuous Positive Airway Pressure (CPAP) is a device to maintain positive pressure in the neonate's airway as long as it can breathe spontaneously. FiO2 percentage, flowmeter, humidifier mode, PEEP depth are parameters that must be set for oxygen therapy using a cpap bubble device, but this tool has minimal monitoring. It has been developed by several previous researchers but has several shortcomings, namely there is no digital result display, no measurement of oxygen rate, oxygen concentration, temperature and humidity. The purpose of this research is to design a parameter monitoring tool on the cpap bubble so that it can monitor the baby's condition in real time and can be used as an indicator of achieving the desired concentration setting. The contribution in this study is a monitoring system or remote monitoring so that nurses and doctors can monitor the baby's condition even though they are not accompanying him. In order to facilitate the process of monitoring and diagnosing patients, a parameter monitoring tool on the cpap bubble based on the Internet of Things is made with notifications on telegrams so that patients can be treated quickly. The design of this tool uses OCS-3f as a sensor for detecting oxygen concentration and DHT22 as a sensor for detecting humidity. The output of oxygen and humidity concentrations is then processed by the ESP32 microcontroller into the ADC pin. Data that has been processed from analog sensor data into digital data on the ESP32 is then sent to the https://thinger.io site using the internet network via the wifi module contained in the ESP32 module build-in. In measuring positioned in the settings of 21% to 95%. The largest error value obtained is 4.6% and the smallest is 0.04%.